Energy consumption of diesel hybrid electric bus simulated from different drive modes - Jirawat Boonjun; Woradej Manosroi; Niti Kammuang-lue (Energy Reports, 2022)
The fuel and energy consumptions between different drive modes of the diesel hybrid electric bus were simulated and compared in this study. The simulated consumptions from two different hybrid modes were compared to the one obtained from the pure diesel mode and the pure electric mode. The backward simulation scheme was used to determine the required traction power of vehicles at specified vehicle velocity and time entire the driving cycle defined in the EPA heavy duty urban dynamometer driving schedule. The summation of fuel consumption of diesel engine, which was referred to the theoretical model of the diesel cycle, and the electric energy consumption of the motor were set as the total energy consumption at a certain specified time of the diesel hybrid electric bus. The conclusion showed that the combination of the drive mode with higher percentage of motorized power can reduce the summation of energy consumption and the energy cost of the diesel hybrid electric bus.